Drosophila suzukii (Diptera: Drosophilidae) arrives at Minas Gerais state, a main strawberry production region in Brazil - Felipe, Andreazza; Khalid, Haddi; Eugênio, E. Oliveira; João, Alfredo M. Ferreira (Florida Entomological Society, 2016)
Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) was first collected in Minas Gerais State, Brazil, in Mar 2016, in the municipality of Ervália, from an organic strawberry field. In Brazil, this pest was first recorded in the southernmost region, in Rio Grande do Sul and Santa Catarina states. Drosophila suzukii's arrival to Minas Gerais State, about 1,500 km north from its first record, should alarm the growers, the research community, and the authorities, because this region is the main strawberry production region in Brazil and is now susceptible to large increases in production losses caused by this invasive species. The lack of alternative effective management tools for D. suzukii, besides traditional chemical sprays, makes this pest an important area of study. Future research should focus on finding strategies that match with different local growing systems and edaphoclimatic conditions.

Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) foi primeiramente coletada no estado de Minas Gerais em Março de 2016, no município de Ervália, em uma produção orgânica de morangos. No Brasil, esta praga foi primeiramente encontrada na região do extremo sul, nos estados do Rio Grande do Sul e Santa Catarina. A chegada de D. suzukii à Minas Gerais, aproximadamente 1.500 km ao norte do seu primeiro registro, deve alertar os produtores, a comunidade cientifica e autoridades, já que esta região é a principal região produtora de morangos do Brasil e agora está suscetível à aumentos nas perdas da produção causadas por essa espécie invasiva. A falta de ferramentas de manejo efetivas alternativas para D. suzukii, além do controle químico tradicional, torna esta praga um importante objeto de estudo. Pesquisas futuras deverão focar em encontrar ferramentas que combinem com diferentes sistemas de produção e condições edafoclimáticas locais.
Keywords: Spotted wing drosophila; First record; Invasive pest; Crop protection; Drosófila-da-asa-manchada; Primeiro relato; Praga invasiva; Fitossanidade